2006
DOI: 10.1097/00000478-200604000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma-Like Posttransplant Lymphoproliferative Disorder (HL-Like PTLD) Simulates Monomorphic B-Cell PTLD Both Clinically and Pathologically

Abstract: Although Hodgkin lymphoma-like posttransplantation lymphoproliferative disorder (HL-like PTLD) has been grouped with classic Hodgkin lymphoma type PTLD (HL-PTLD), controversy remains as to whether it is truly a form of HL or whether it should be more appropriately classified as a form of B-cell PTLD. Because only few cases of HL-like PTLD have been reported, their pathologic nature and clinical behavior have not been well defined. This report characterized 5 cases of HL-like PTLD with respect to their immunoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Rare cases of classical Hodgkin lymphoma-type PTLD occur late after transplant (beyond the first year) and invariably contain EBV within the malignant Reed-Sternberg/Hodgkin cells (148). The immunophenotype is that of nodular sclerosis or mixed cellularity Hodgkin lymphoma, and response to therapy is generally favorable (174).…”
Section: Classical Hodgkin Lymphoma-type Ptld and Other Rare Variantsmentioning
confidence: 99%
“…Rare cases of classical Hodgkin lymphoma-type PTLD occur late after transplant (beyond the first year) and invariably contain EBV within the malignant Reed-Sternberg/Hodgkin cells (148). The immunophenotype is that of nodular sclerosis or mixed cellularity Hodgkin lymphoma, and response to therapy is generally favorable (174).…”
Section: Classical Hodgkin Lymphoma-type Ptld and Other Rare Variantsmentioning
confidence: 99%
“…Limited observations of the clinical outcome suggested that HLlike PTLD is an aggressive disorder like a true B-cell type PTLD. 35 This is a very rare disease and it is difficult to collect evidence that would unequivocally demonstrate that such cases should be distinguished from CHL-type PTLD. However, it was suggested that CHL-type PTLD may respond best to chemotherapies often used in CHL, whereas an HL-like PTLD may be more amenable to combinations of chemo-immunotherapy often used for NHL.…”
Section: Monomorphic Ptldmentioning
confidence: 99%
“…A total of 21 international published studies [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were found that met our criteria. Table 1 summarizes data of the enrolled studies.…”
Section: Study Populationmentioning
confidence: 99%